Developmental Pathway Choices of Young People Presenting to a Gender Service with Gender Distress: A Prospective Follow-Up Study - Joseph Elkadi; Catherine Chudleigh; Ann M. Maguire; Geoffrey R. Ambler; Stephen Scher; Kasia Kozlowska (MDPI AG, 2023)
This prospective case-cohort study examines the developmental pathway choices of 79 young people (13.25-23.75 years old; 33 biological males and 46 biological females) referred to a tertiary care hospital's Department of Psychological Medicine (December 2013-November 2018, at ages 8.42-15.92 years) for diagnostic assessment for gender dysphoria (GD) and for potential gender-affirming medical interventions. All of the young people had attended a screening medical assessment (including puberty staging) by paediatricians. The Psychological Medicine assessment (individual and family) yielded a formal DSM-5 diagnosis of GD in 66 of the young people. Of the 13 not meeting DSM-5 criteria, two obtained a GD diagnosis at a later time. This yielded 68 young people (68/79; 86.1%) with formal diagnoses of GD who were potentially eligible for gender-affirming medical interventions and 11 young people (11/79; 13.9%) who were not. Follow-up took place between November 2022 and January 2023. Within the GD subgroup (n = 68) (with two lost to follow-up), six had desisted (desistance rate of 9.1%; 6/66), and 60 had persisted on a GD (transgender) pathway (persistence rate of 90.9%; 60/66). Within the cohort as a whole (with two lost to follow-up), the overall persistence rate was 77.9% (60/77), and overall desistance rate for gender-related distress was 22.1% (17/77). Ongoing mental health concerns were reported by 44/50 (88.0%), and educational/occupational outcomes varied widely. The study highlights the importance of careful screening, comprehensive biopsychosocial (including family) assessment, and holistic therapeutic support. Even in highly screened samples of children and adolescents seeking a GD diagnosis and gender-affirming medical care, outcome pathways follow a diverse range of possibilities.